STUDI ANALISA TEBAL PERKERASAN PADA HALAMAN PARKIR FAKULTAS HUKUM DAN EKONOMI UNIVERSITAS 17 AGUSTUS 1945 SAMARINDA - PUTRA, YANUAR ARDIAN (KURVA S JURNAL MAHASISWA, 2018)
Road pavement is a layer that is located on the subgrade that has been compiled, which serves to carry the load of traffic then spread the load, both horizontally and vertically and finally forward the load to the subgrade so that the load on the subgrade does not exceed the carrying capacity of the soil. The pavement layer of a road consists of one or several layers of rock material and bonding material. Some types of road pavement that are known today are rigid pavement, flexible pavement and composite pavement.Parking yard of the Faculty of Law and Economy of the Universitas 17 Augustus 1945 Samarinda is one of the supporting facilities that are also planned along with the construction of a new building on the faculty. Considering the ground level of the old parking lot level of the university was still low so that when receiving rainwater runoff it takes a long time to dry, so in planning the parking yard in the Faculty of Law and Economics it is necessary to be counted to get the best quality also effective and efficient products from economic aspectData collection in the field is the parking yard location data,average daily traffic data (LHR) and documentation. Other supporting data, obtained from related institutions. While the calculation method used used the Bina Marga method (Pd-T-14-2003) for rigid pavement types and Component Analysis methods for flexible pavement types.From the results of the calculation it can be concluded that the analysis of thickness pavement on the parking lot of the Faculty of Law and Economy of the Universitas 17 Augustus 1945 Samarinda with a rigid pavement type is obtained 19 cm concrete plate thickness using Concrete K-250 while the flexible pavement type obtained thickness of the surface layer is 4 cm using Laston MS-744 with a foundation layer using 15 cm Class A Aggregate.